2004
DOI: 10.1016/s1010-7940(03)00652-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of complement and leukocyte receptors during on- and off pump coronary artery bypass surgery

Abstract: This prospective, randomised study showed less complement activation in low risk OFFCAB, compared to ONCAB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 22 publications
2
42
1
2
Order By: Relevance
“…The mechanism includes impairment of glomerular filtration and tubular function due to system inflammatory response associated with the use of extracorporeal circulation, non-pulsatile flow of the extracorporeal circulation, haemodilution, possible hypoperfusion of the kidneys, atheroembolization and other causes 5,6 . The systemic inflammatory response develops also following surgery without extracorporeal circulation in contrast to the procedures with EC, however the reaction is not so serious and the final effect on the renal functions is less serious 19,20 . Haemodilution and non-pulsatile flow are specific characteristics of the extracorporeal circulation and they do not occur during the OPCABG procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism includes impairment of glomerular filtration and tubular function due to system inflammatory response associated with the use of extracorporeal circulation, non-pulsatile flow of the extracorporeal circulation, haemodilution, possible hypoperfusion of the kidneys, atheroembolization and other causes 5,6 . The systemic inflammatory response develops also following surgery without extracorporeal circulation in contrast to the procedures with EC, however the reaction is not so serious and the final effect on the renal functions is less serious 19,20 . Haemodilution and non-pulsatile flow are specific characteristics of the extracorporeal circulation and they do not occur during the OPCABG procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Rasmussen et al [24] and Parolari [25] and Wehlin [26] reported no difference in IL-6 or hs-CRP following randomization to CCAB or OPCAB. Chowdhury et al [27] demonstrated a significant increase in hs-CRP among CCAB in the on-pump group compared to the offpump surgical arm, but questioned the diagnostic ability of hs-CRP for myocardial damage.…”
Section: Biomarkers Of the Systemic Inflammatory Responsementioning
confidence: 98%
“…Bu nedenle eş zamanlı kalp damar hastalığı ve akciğer kanseri olgularının doğru bir şekilde değerlendirilmesi tam olarak yapılamamaktadır. 2000'li yıllardan itibaren her iki hastalığın eş zamanlı tedavi protokolleri güncellen-mekte ve çoğunlukla uygulanabilir bulunmaktadır (6)(7)(8) Yayınlarda özellikle kalp akciğer pompası kullanımı, yaklaşım türü ve tümörün pompa aracılığıyla yayılımı değerlendirilmektedir (9)(10)(11)(12)(13)(14)(15).…”
Section: Görülme Sikliği (Incidense)unclassified